2019
DOI: 10.1109/jsen.2019.2938764
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Gait Feedback Method Based on Wearable Inertial Sensors for a Drop Foot Assistance Device

Abstract: To maximise the efficiency of gait interventions, gait phase and joint kinematics are important for closing the system loop of adaptive robotic control. However, few studies have applied an inertial sensor system including both gait phase detection and joint kinematic measurement. Many algorithms for joint measurement require careful alignment of the inertial measurement unit (IMU) to the body segment. In this paper, we propose a practical gait feedback method, which provides sufficient feedback without requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…Soft-tissue artifacts have been found to be a source of noise in data processing [43], [66]. Some studies that used multiple IMUs were required to perform sensor-to-segment alignment and calibration [45], [92] to achieve better performance. This may increase the preparation time but is comparatively faster than using marker-based systems.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Soft-tissue artifacts have been found to be a source of noise in data processing [43], [66]. Some studies that used multiple IMUs were required to perform sensor-to-segment alignment and calibration [45], [92] to achieve better performance. This may increase the preparation time but is comparatively faster than using marker-based systems.…”
Section: Discussionmentioning
confidence: 99%
“…8) Integration of wearable sensor gait analysis and feedback system: In this review, several studies were found to analyze the data from wearable sensors and provide them as feedback to the user through various modalities such as audio, visual, and haptic feedback [54], [63], [92], [94]. Feedback strategies are needed for gait retraining or real-time assessment to correct certain parameters in rehabilitation or sports applications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(multilayer) perceptron models 28,42,49,51,77 , as well as random forest classifiers 36,42,44 , K-nearest neighbours 42,54,78 , and other types of machine learning using, e.g., Bayesian models 31,32,73,76 , Gaussian mixture model 41 , and principal component analysis 39,40,51,73 . Echo state networks have the great advantage of low computational costs while still showing excellent performance.…”
Section: Discussionmentioning
confidence: 99%